OPTIMASI PENGELOLAAN USAHA PERIKANAN TANGKAP DI KEPULAUAN TOGEAN KABUPATEN TOJO UNA-UNA - Laapo, Alimudin (FAPETKAN UNTAD, 2011)
The utilization of the fishery potency of Tojo Una-Una Regency has not been optimum resulting in the low income of fisherman. The research was aimed to optimize capture fisheries management (economic and ecology sustainability) Data used in this study included Maximum Sustainable Yield (MSY) and primary data analyzed by using Linear Goal Programming Method. Results showed that the optimal number of catch fishery effort unit operated in the marine area of Tojo Una-Una Regency consisted of 197 gillnet units, 132 liftnet units, 235 handline units, 33 roll line units and 16 purse seine units. The management of this fishery effort would meet the targets of fisherman maximum income which was IDR 17.56 billion, domestic income which was IDR 780 million, fish consumption which was 6.775,92 ton and also could employ 32,87% labour. The use of catch fishery resources reached a level of 99-100% (indicated overfishing).